Resin composition
By using a combination of modified maleimide resin, benzooxazine resin and epoxy resin in the resin composition, the problem of difficulty in meeting the short circuit test, low water absorption and low dielectric characteristics at the same time is solved, and the competitiveness of the electronic substrate is improved.
Patent Information
- Application Number
- CN202311262468.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-04
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-04
AI Technical Summary
The prior art is difficult to meet the requirements of short-circuit testing, low water absorption and low dielectric characteristics of printed circuit boards at the same time, resulting in insufficient reliability and electrical performance of electronic substrates.
A resin composition is adopted, including modified maleimide resin, benzooxazine resin and epoxy resin. By modifying the molecular structure of maleimide resin and combining it with other resins, it can meet the requirements of short-circuit testing, low water absorption and low dielectric characteristics.
It achieves the requirements of short-circuit testing, low water absorption and low dielectric characteristics at the same time, making the manufactured electronic substrates competitive, and the reliability and electrical performance have been improved.
Smart Images

Figure BDA0004473384160000041 
Figure BDA0004473384160000055 
Figure BDA0004473384160000081
Abstract
Description
Technical Field
[0001] The invention relates to a resin composition. Background Art
[0002] In recent years, with the development of 5G communications, the requirements for the reliability and electrical performance of electronic substrates such as printed circuit boards have gradually increased. Therefore, it is an urgent goal for technicians in this field to develop a resin composition that can meet the requirements of short-circuit tests (such as CAF (Conductive Anodic Filament) tests), low water absorption and low dielectric properties, so that the electronic substrates manufactured can be competitive. Summary of the invention
[0003] The present invention provides a resin composition which can simultaneously meet the requirements of short circuit test, low water absorption and low dielectric properties, so as to be competitive.
[0004] A resin composition of the present invention comprises a resin. The resin comprises a benzoxazine resin, an epoxy resin and a modified maleimide resin. The modified maleimide resin is formed by a condensation polymerization reaction of a dicyclopentadiene resin having an amino group and maleic anhydride, and the dicyclopentadiene resin having an amino group is formed by a nitration reaction and a hydrogenation reaction of a dicyclopentadiene phenolic resin.
[0005] In one embodiment of the present invention, the modified maleimide resin has the following structural formula: Wherein L represents a dicyclopentadienyl group, a divalent organic group derived from a phenolic compound, or a combination thereof, 1 and L 2 Each represents a divalent organic group derived from a phenolic compound, and m represents an integer of 0 to 18.
[0006] In one embodiment of the present invention, the weight ratio of the modified maleimide resin to the resin ranges from 40 wt % to 80 wt %.
[0007] In one embodiment of the present invention, the weight ratio of the benzoxazine resin to the resin ranges from 10 wt % to 30 wt %.
[0008] In one embodiment of the present invention, the weight ratio of the epoxy resin to the resin ranges from 5 wt % to 20 wt %.
[0009] In one embodiment of the present invention, the above-mentioned catalyst, flame retardant, silicon dioxide, siloxane coupling agent or a combination thereof.
[0010] In one embodiment of the present invention, the usage amount of the catalyst is between 0.05 phr and 2 phr.
[0011] In one embodiment of the present invention, the usage amount of the flame retardant is between 10 phr and 30 phr.
[0012] In one embodiment of the present invention, the weight ratio of the silicon dioxide is in a range of 30 wt % to 50 wt %.
[0013] In one embodiment of the present invention, the usage amount of the siloxane coupling agent is between 0.1 phr and 5 phr.
[0014] Based on the above, the resin composition of the present invention uses maleimide resin (Bismaleimide, BMI) which performs well in the short circuit test as the main framework system, and in order to have good dielectric properties and water absorption, the resin composition of the present invention further modifies the molecular structure of the maleimide resin to obtain a modified maleimide resin whose main chain includes a dicyclopentadiene structure, and combines it with other resins (such as benzoxazine resin, epoxy resin), so that the requirements of short circuit test, low water absorption and low dielectric properties can be met at the same time, making it competitive.
[0015] In order to make the above features and advantages of the present invention more obvious and easy to understand, embodiments are specifically described in detail below. DETAILED DESCRIPTION
[0016] Hereinafter, embodiments of the present invention will be described in detail. However, these embodiments are illustrative only, and the present invention is not limited thereto.
[0017] In this article, the range expressed as "between a value and another value" is a summary expression method to avoid listing all the values in the range one by one in the specification. Therefore, the description of a specific numerical range, if not specifically stated, covers the endpoint values, any value in the numerical range, and a smaller numerical range defined by any value in the numerical range, just as if the arbitrary value and the smaller numerical range were written in the specification.
[0018] Herein, the so-called “divalent organic group” is an organic group having two bonding positions, and the “divalent organic group” can form two chemical bonds through the two bonding positions.
[0019] In the present embodiment, resin composition includes resin, wherein resin includes benzoxazine (Benzoxazine) resin, epoxy resin (epoxy) and modified maleimide resin. In addition, modified maleimide resin is formed by condensation polymerization of dicyclopentadiene resin and maleic anhydride with amino group, and dicyclopentadiene resin with amino group is formed by nitration reaction and hydrogenation reaction of dicyclopentadiene phenolic resin. Accordingly, the resin composition of the present invention selects the maleimide resin with excellent performance in short circuit test as the main framework system, and in order to have good dielectric properties and water absorption, the resin composition of the present invention further modifies the molecular structure of maleimide resin to obtain the modified maleimide resin (dicyclopentadiene maleimide, DCPD-BMI) including dicyclopentadiene structure in the main chain, and it is combined with other resins (such as benzoxazine resin, epoxy resin), so that the requirements such as short circuit test, low water absorption and low dielectric properties can be met simultaneously, so that it can be competitive.
[0020] Furthermore, by selecting and modifying the resins of the present invention, synergistic effects are generated in the molecular structures of the resins. This can avoid the situation in which the current applications (such as low dielectric copper clad laminates) use polyphenylene ether (PPE) as the main framework system to have poor performance in short circuit tests, and can also effectively improve the reliability performance of unmodified maleimide resins. For example, the glass transition temperature of the substrate made of the resin composition of the present invention is greater than 220°C, the dielectric constant (Dk) is between 3.3 and 3.7, and the dielectric loss (Df) is less than 0.004, but the present invention is not limited to this.
[0021] In some embodiments, the resin composition may not include polyphenylene ether resin to further reduce the adverse effects of polyphenylene ether resin on the short circuit test, but the present invention is not limited thereto.
[0022] The specific details of modifying the maleimide resin, benzoxazine resin and epoxy resin will be described in detail below.
[0023] Modified maleimide resin
[0024] In some embodiments, specific examples of commercially available products of dicyclopentadiene resins having a phenolic group may include ERM6140 (trade name; manufactured by Songyuan Company, weight average molecular weight 1,300), ERM6105 (trade name; manufactured by Songyuan Company, weight average molecular weight 800), ERM6115 (trade name; manufactured by Songyuan Company, weight average molecular weight 1,100) or other suitable dicyclopentadiene phenolic resins.
[0025] In some embodiments, the weight ratio of the modified maleimide resin to the resin ranges from 40 wt % to 80 wt %, but the present invention is not limited thereto.
[0026] Preparation method of modified maleimide resin
[0027] First, dicyclopentadiene phenolic resin is first subjected to nitration and hydrogenation to form a dicyclopentadiene resin with an amino group. The method for nitration and hydrogenation of dicyclopentadiene phenolic resin is not particularly limited, for example, well-known nitration and hydrogenation methods can be used, which are not described separately here. Then, the dicyclopentadiene resin with an amino group and maleic anhydride are subjected to condensation polymerization to form a modified maleimide resin. In the present embodiment, the equivalent ratio of the molar number of the amino group of the dicyclopentadiene resin with an amino group to the molar number of the maleic anhydride group of maleic anhydride is 1:1 to 1:10, preferably 1:1 to 1:3.
[0028] The modified maleimide resin has a structure represented by the following formula (1): In this embodiment, the weight average molecular weight of the modified maleimide resin is 800 to 10,000, preferably 1,000 to 4,000.
[0029]
[0030] In formula (1), L represents a dicyclopentadienyl group, a divalent organic group derived from a phenolic compound, or a combination thereof, preferably a combination of a dicyclopentadienyl group and a divalent organic group derived from a phenolic compound, and the divalent organic group is preferably a divalent organic group including a maleimide group;
[0031] L 1 and L 2 each represents a divalent organic group derived from a phenolic compound; and
[0032] m represents an integer of 0-18, preferably 2-10.
[0033] L, L 1 and L 2 may represent a divalent organic group derived from phenol. In this embodiment, L may represent or a combination thereof, preferably and Combination of; * indicates the bonding position. 1 and L 2 Can be expressed separately *Indicates the bonding position.
[0034] In this embodiment, the modified maleimide resin may have a structure represented by the following formula (2): In this embodiment, the modified maleimide resin is a modified multi-maleimide resin.
[0035]
[0036] In formula (2), m represents an integer of 0 to 18, preferably 2 to 10.
[0037] Benzoxazine resin and epoxy resin
[0038] In some embodiments, the benzoxazine resin can be any suitable commercially available BZ resin, which is not limited by the present invention. The epoxy resin can also be classified into various epoxy resins according to the main skeleton. The above-mentioned epoxy resins can be further classified into: bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin and other bisphenol type epoxy resins; biphenyl aralkyl novolac epoxy resin, phenol novolac epoxy resin, alkylphenol novolac epoxy resin, cresol novolac epoxy resin; Epoxy resins, naphthol alkylphenol copolymer phenolic varnish type epoxy resins, naphthol aralkyl cresol copolymer phenolic varnish type epoxy resins, bisphenol A phenolic varnish type epoxy resins, bisphenol F phenolic varnish type epoxy resins and other phenolic varnish type epoxy resins; stilbene type epoxy resins; epoxy resins containing triazine skeletons; epoxy resins containing fluorene skeletons; naphthalene type epoxy resins; anthracene type epoxy resins; triphenylmethane type epoxy resins; biphenyl type epoxy resins; xylene type epoxy resins; dicyclopentadiene type epoxy resins and other alicyclic epoxy resins, etc.
[0039] In some embodiments, the weight ratio of the benzoxazine resin to the resin ranges from 10 wt % to 30 wt %, but the present invention is not limited thereto.
[0040] In some embodiments, the weight ratio of the epoxy resin to the resin ranges from 5 wt % to 20 wt %, but the invention is not limited thereto.
[0041] In some embodiments, only modified maleimide resin is used in the resin composition. In other words, the resin composition may not include unmodified maleimide resin to achieve better water absorption and dielectric properties, but the present invention is not limited thereto. In other embodiments, according to actual product application requirements, the resin composition may further include unmodified maleimide resin, that is, the resin composition may simultaneously use unmodified maleimide resin and the modified maleimide resin, wherein the unmodified maleimide resin may be commercially available BMI-50P, KI-70 or the like, but the present invention is not limited thereto.
[0042] In some embodiments, when the resin composition includes unmodified maleimide resin, the total weight ratio of the unmodified maleimide resin and the modified maleimide resin to the resin ranges from 40 wt % to 80 wt %, but the present invention is not limited thereto.
[0043] In some embodiments, the resin composition further includes a catalyst, a flame retardant, silicon dioxide, a siloxane coupling agent or a combination thereof, wherein the amount of the catalyst is between 0.05 phr and 2 phr; the amount of the flame retardant is between 10 phr and 30 phr; based on the weight of the resin, the flame retardant and the silicon dioxide, the weight ratio of silicon dioxide is between 30 wt% and 50 wt%; and the amount of the siloxane coupling agent is between 0.1 phr and 5 phr, but the present invention is not limited thereto. Here, the unit phr can be defined as the weight of other materials added to every 100 weight parts of the resin in the resin composition, and the weight ratio of silicon dioxide is based on the weight of the resin in the resin composition plus the weight of the flame retardant.
[0044] In some embodiments, the catalyst may be 2-ethyl 4-methylimidazole (2E4MZ; CAS: 931-36-2; ), to catalytically drive the resin to have better reactivity during the thermal curing process, but the present invention is not limited thereto.
[0045] In some embodiments, the flame retardant is a halogen-free flame retardant and a specific example can be a phosphorus-based flame retardant, which can be selected from phosphate esters, such as triphenyl phosphate (TPP), resorcinol bisphosphate (RDP), bisphenol A di(diphenyl) phosphate (BPAPP), bisphenol A di(dimethyl) phosphate (BBC), resorcinol diphosphate (CR-733S), resorcinol-bis(di-2,6-dimethylphenyl phosphate) (PX-200); can be selected from phosphazenes, such as polydi(phenoxy)phosphazene (SPB-100); ammonium polyphosphates, melamine phosphates (MPP, i.e. Melamine Polyphosphate), melamine cyanurate (Melamine cyanurate); one or more combinations of DOPO-type flame retardants, such as DOPO (such as structural formula (C)), DOPO-HQ (such as structural formula (D)), double DOPO derivative structure (such as structural formula (E)), etc.; aluminum-containing hypophosphites (such as structural formula (F)).
[0046]
[0047] In some embodiments, the silica is spherical silica and can be prepared using a synthetic method to reduce electrical properties and maintain fluidity and filling properties, wherein the spherical silica has a surface modification of acrylic or vinyl, a purity of about 99.0% or more, and an average particle size D50 of about 2.0 micrometers (μm) to 3.0 μm, but the present invention is not limited thereto, and silica can also be prepared using other suitable methods.
[0048] In some embodiments, the siloxane coupling agent may include but is not limited to siloxane compounds. In addition, according to the type of functional group, it can be divided into amino silane compounds, epoxy silane compounds, vinyl silane compounds, ester silane compounds, hydroxyl silane compounds, isocyanate silane compounds, methacryloxy silane compounds and acryloxy silane compounds to enhance the compatibility and crosslinking degree of the glass fiber cloth and the powder in the circuit board, but the present invention is not limited thereto.
[0049] It should be noted that the resin composition of the present invention can be processed into a prepreg and a copper foil substrate (CCL) according to actual design requirements, and the specific implementations listed above are not limitations of the present invention. As long as the resin composition includes them, they all fall within the protection scope of the present invention.
[0050] The following examples and comparative examples are listed to illustrate the effects of the present invention, but the scope of the present invention is not limited to the scope of the examples.
[0051] The copper foil substrates produced in the examples and comparative examples were evaluated according to the following methods.
[0052] The glass transition temperature (°C) was measured by dynamic mechanical analyzer (DMA).
[0053] Water absorption (%): After the sample is heated in a pressure cooker at 120°C and 2 atm for 120 minutes, the weight change before and after heating is calculated.
[0054] 288℃ solder resistance (seconds): The sample is heated in a pressure cooker at 120℃ and 2atm for 120 minutes and then immersed in a 288℃ solder furnace. The time required for the sample to explode and delaminate is recorded.
[0055] Dielectric constant Dk: The dielectric constant Dk was measured at a frequency of 10 GHz using a dielectric analyzer (HP Agilent E4991A).
[0056] Dielectric loss Df: The dielectric loss Df at a frequency of 10 GHz was measured using a dielectric analyzer (HP Agilent E4991A).
[0057] CAF test: The copper foil substrate was tested under the following conditions: temperature and humidity 85°C / 85% RH, voltage 50V, time>1000 hours, pore size: 0.35mm, pore spacing: 0.3mm.
[0058] <Examples 1 to 3, Comparative Examples 1 to 2>
[0059] The resin composition shown in Table 1 was mixed with toluene to form a varnish of a thermosetting resin composition. The varnish was impregnated with Nan Ya fiberglass cloth (Nan Ya Plastics Co., Ltd., cloth type 1078LD) at room temperature, and then dried at 130°C (impregnation machine) for several minutes to obtain a prepreg with a resin content of 70wt%. Finally, four prepregs were stacked between two 35μm thick copper foils and heated at 25kg / cm 2 The pressure and temperature were kept constant for 20 minutes at 85°C, and then heated to 210°C at a heating rate of 3°C / min, and then kept constant for 120 minutes, and then slowly cooled to 130°C to obtain a 0.59 mm thick copper foil substrate. Here, the modified maleimide resin in Table 1 was prepared in the following manner. A dicyclopentadiene phenolic resin (trade name ERM6140, manufactured by Songyuan Company, with a weight average molecular weight of about 1,300) containing about 1 mol of hydroxyl group and about 1.25 mol of 4-halonitrobenzene (the halogen can be fluorine, chlorine, bromine or iodine) were added to about 6 mol of dimethylacetamide (DMAC) as a reaction solvent, and reacted at a temperature of about 120°C for about 300 minutes to perform a nitration reaction. Then, hydrogen was introduced and reacted at a temperature of about 90°C for about 480 minutes to perform a hydrogenation reaction to form a dicyclopentadiene resin having an amino group. Next, about 3 mol of maleic anhydride and about 9.7 wt % of toluenesulfonic acid were added, and the mixture was reacted at a temperature of about 120° C. for about 420 minutes to obtain the modified maleimide resin in Table 1, which is a maleimide resin including a dicyclopentadiene structure in the main chain (i.e., homemade DCPD-MI) and having The structure represented by (m represents an integer from 0 to 18).
[0060] The physical properties of the copper foil substrates were tested, and the results are shown in Table 1. By comparing the results of Examples 1 to 3 and Comparative Examples 1 to 2 in Table 1, the following conclusions can be drawn: Comparative Example 1 is a polyphenylene ether-based system, which performs poorly in the short circuit (CAF) test and is prone to short circuit conduction problems. Comparative Example 2 uses only unmodified maleimide resin, so it also performs poorly in water absorption and dielectric properties. Examples 1 to 3 all pass the short circuit test and have low water absorption and low dielectric properties.
[0061] Table 1
[0062]
[0063]
[0064] In summary, the resin composition of the present invention uses maleimide resin that performs well in the short circuit test as the main framework system, and in order to have good dielectric properties and water absorption, the resin composition of the present invention further modifies the molecular structure of the maleimide resin to obtain a modified maleimide resin whose main chain includes a dicyclopentadiene structure, and combines it with other resins (such as benzoxazine resin, epoxy resin), so that the requirements of short circuit test, low water absorption and low dielectric properties can be met at the same time, making it competitive.
[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A resin composition, characterized in that: include: Resins, including: Benzoxazine resins; Epoxy resin; and The modified maleimide resin is prepared by condensation polymerization of a dicyclopentadiene resin having an amino group and maleic anhydride, and the dicyclopentadiene resin having an amino group is prepared by nitration and hydrogenation of a dicyclopentadiene phenolic resin.
2. The resin composition according to claim 1, characterized in that The modified maleimide resin has the following structural formula: Wherein L represents a dicyclopentadienyl group, a divalent organic group derived from a phenolic compound, or a combination thereof, 1 and L 2 Each represents a divalent organic group derived from a phenolic compound, and m represents an integer of 0 to 18.
3. The resin composition according to claim 1, characterized in that The weight ratio of the modified maleimide resin to the resin ranges from 40wt% to 80wt%.
4. The resin composition according to claim 1, characterized in that The weight ratio of the benzoxazine resin to the resin ranges from 10 wt % to 30 wt %.
5. The resin composition according to claim 1, characterized in that The weight ratio of the epoxy resin to the resin ranges from 5wt% to 20wt%.
6. The resin composition according to claim 1, characterized in that The invention further comprises a catalyst, a flame retardant, silicon dioxide, a siloxane coupling agent or a combination thereof.
7. The resin composition according to claim 6, characterized in that The catalyst is used in an amount ranging from 0.05 phr to 2 phr.
8. The resin composition according to claim 6, characterized in that The flame retardant is used in an amount ranging from 10 phr to 30 phr.
9. The resin composition according to claim 6, characterized in that The weight proportion of the silicon dioxide is in a range of 30 wt % to 50 wt %.
10. The resin composition according to claim 6, characterized in that The usage amount of the siloxane coupling agent is between 0.1 phr and 5 phr.